Comparison of pancreatic respiratory motion management with three abdominal corsets for particle radiation therapy: case study - Dolde, Kai; Schneider, Sergej; Stefanowicz, Sarah; Alimusaj, Merkur; Flügel, Beate; Saito, Nami; Troost, Esther G. C.; Pfaffenberger, Asja; Hoffmann, Aswin L. (Journal of applied clinical medical physics, 2019)
Background and purpose - Abdominal organ motion seriously compromises the targeting accuracy for particle therapy in patients with pancreatic adenocarcinoma. This study compares three different abdomi...
Gesehen am 19.02.2020